SQ3R Method as an Alternative Pedagogical Strategy to Enhance Students’ Reading Comprehension - Sofyan, Nurlaily; Farsha Basyarewan (Eduvelop: Journal of English Education and Development, 2025)
SQ3R Method is systematic method that can enhance students’ reading comprehension. This method has five steps that should completely implement it. Firstly, survey step which we are surveying the table of contents and the tittle of the book or text will be read. Secondly, question step which we are questioning the unclear sentences in the previous step. The last step is 3R (Read, Recite and Review). Read is the main step of this method which we are reading the whole text. Recite step is the step which we must jot down the answers of unclear sentences we met before. And the last step is Review which we try to conclude what we read and write. The design of this research is descriptive research. The samples are from the first semester of English Department students at UMMU amounted to18 students. The students are following the research as long as 7 meetings and they are reading 6 texts and answering 30 questions of pre-test and post-test given by the researchers. Three students are interviewed by the researchers and they are asked 10 of interview questions. The result of the research showed that the students’ reading comprehension through SQ3R method at English Department of UMMU is in the good category. Dealing with the score that the students achieve, it can be seen from the result of the test that is 66.45%. According to the result, it can be seen that the implementation of SQ3R method has been enhancing students’ reading comprehension because the students could understand the steps of the method itself although this is still a new method for them.